Incessant Industrial Disharmony and Employees’ Distress in Nigerian Tertiary Institutions: A Coping Strategy for University Lecturers - Idris, Abu; Abdulkadir, Abdulmalik; Bashir, Bashir Musa; Shehu, Ahmed (Kashere Journal of Politics and International Relations, 2024)
Industrial disharmonies are perennial event that occupies historic position in the organization and a recurring decimal in Nigeria. The inability of government to fulfill its agreements particularly with Academic Staff Union of University led to the frequent strikes in spite of their contribution to educational development. However, proclamation of “no work no pay” has frustrated lecturers particularly that majority rely on salary for survival. It is against this background that this study adopts qualitative method using interview and content analysis to assess the effect of industrial disharmony on the lecturers and to as well explore coping strategies to sustain the lecturers during the industrial strikes. The analysis demonstrates that incessant strike has exposed the lecturers to untold financial hardship, emotional distress, and professional stagnation. The study reveals that the financial hardship is as a result of lecturers’ refusal to plan, save for emergency funds, high expenses, debt, focus on short-term needs over long-term security, wrong assumption that salaries will always be consistent, underfunding of the system, poor salary and proliferation of politically motivated universities contributed immensely to lecturer hardships. In order to cope with the hardships during the industrial strike, this study recommend that lecturers should diversify income streams such as consultancy services, engage in local and international research collaborations to expand professional networks and create potentially opportunities; develop entrepreneurial skills in others disciplines like farming, business, build an emergency fund, (saving); engage in online communities and networking, foster a support network; open to new opportunities and challenges among others.